Growing sense of social status threat and concomitant deaths of despair among whites - Arjumand Siddiqi; Odmaa Sod-Erdene; Darrick Hamilton; Tressie McMillan Cottom; William Darity, Jr (Elsevier, 2019)
Background: A startling population health phenomenon has been unfolding since the turn of the 21st century. Whites in the United States, who customarily have the most favorable mortality profile of all racial groups, have experienced rising mortality rates, without a commensurate rise in other racial groups. The two leading hypotheses to date are that either contemporaneous economic conditions or longer-term (post-1970s) economic transformations have led to declining economic and social prospects of low-educated whites, culminating in "deaths of despair." We re-examine these hypotheses and investigate a third hypothesis: mortality increases are attributable to (false) perceptions of whites that they are losing social status. Methods: Using administrative and survey data, we examined trends and correlations between race-, age- and, education-specific mortality and a range of economic and social indicators. We also conducted a county-level fixed effects model to determine whether changes in the Republican share of voters during presidential elections, as a marker of growing perceptions of social status threat, was associated with changes in working-age white mortality from 2000 to 2016, adjusting for demographic and economic covariates. Findings: Rising white mortality is not restricted to the lowest education bracket and is occurring deeper into the educational distribution. Neither short-term nor long-term economic factors can themselves account for rising white mortality, because parallel trends (and more adverse levels) of these factors were being experienced by blacks, whose mortality rates are not rising. Instead, perceptions - misperceptions - of whites that their social status is being threatened by their declining economic circumstances seems best able to reconcile the observed population health patterns. Conclusion: Rising white mortality in the United States is not explained by traditional social and economic population health indicators, but instead by a perceived decline in relative group status on the part of whites - despite no actual loss in relative group position. Keywords: Race, Mortality, Republican party, Voting, Social determinants of health